A conceptualization of corporate social (ir)responsibility and moral intensity in the supply chain. Issue 3 (23rd September 2019) - Ferguson, Jodie; Brown, Brian; Boyd, D. Eric
Abstract : Purpose: The purpose of this paper is to consider corporate social irresponsibility (CSI) within the supply chain. The discussion focuses on the social component of social responsibility and explores its effects on end-users. Moreover, this paper presents moral intensity, a construct introduced in the ethics literature, as a potential guide to managers who struggle to navigate the gray area between corporate social responsibility (CSR) and CSI. Design/methodology/approach: This paper conceptualizes CSI within the supply chain and offers a framework and propositions for understanding and preventing irresponsible behavior from a moral intensity perspective. Findings: The moral intensity framework provides a normative approach with the potential to guide managers who face choices involving decisions that might lead to irresponsible behavior in interorganizational settings. Originality/value: This paper draws attention to business-to-business CSI and the limited research that focuses on the social aspects of CSR, rather than the environmental and economic factors emphasized in prior research. It also introduces the moral intensity framework to the supply chain literature and highlights the end-user's (i.e. consumer's) role in influencing the performance of the overall value chain.